2021
DOI: 10.1007/s00248-021-01740-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant Biomass and Soil Nutrients Mainly Explain the Variation of Soil Microbial Communities During Secondary Succession on the Loess Plateau

Abstract: Soil microorganisms play an important role in the circulation of materials and nutrients between plants and soil ecosystems, but the drivers of microbial community composition and diversity remain uncertain in different vegetation restoration patterns. We studied soil physicochemical properties (i.e., soil moisture, bulk density, pH, soil nutrients, available nutrients), plant characteristics (i.e., Shannon index [H Plant ] and Richness index [S Plant ], litter biomass [LB], and ne root biomass [FRB]), and mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 52 publications
(81 reference statements)
3
15
0
Order By: Relevance
“…The decrease of soil clay content and the increase of sand content were not conducive to the maintenance of soil moisture and nutrients as well as the growth of vegetation roots, thus affecting the growth of vegetation [40,41]. The decrease of soil moisture content drove the decrease of soil organic carbon (C) and total N content, which led to the decrease of vegetation density and biomass [42]. Soil moisture promoted the growth of plants by increasing the content of soil C, N, bacteria, and fungal PLFA, and fungi had the most important role in promoting vegetation biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of soil clay content and the increase of sand content were not conducive to the maintenance of soil moisture and nutrients as well as the growth of vegetation roots, thus affecting the growth of vegetation [40,41]. The decrease of soil moisture content drove the decrease of soil organic carbon (C) and total N content, which led to the decrease of vegetation density and biomass [42]. Soil moisture promoted the growth of plants by increasing the content of soil C, N, bacteria, and fungal PLFA, and fungi had the most important role in promoting vegetation biomass.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the previous theory that more microbial taxa imply more potential interactions. The increase in complexity of the AMF network from cropland to fallow land may be attributed to the increase in plant diversity, which was regarded as a selective force for soil microbiome assembly and could increase the chance for coevolution ( Xu et al, 2022 ). Moreover, Glomeraceae, Paraglomeraceae, and Archaeosporaceae had the higher values of topological features and were more often located in central ecological positions than other families, indicating their potential roles in maintenance of ecosystem multifunctionality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the decrease in plant diversity in the sown treatments was followed by a decline in the diversity of plant litter and root exudates; a reduction in the heterogeneity of resources may induce a reduction in the fungal diversity [10,64]. On the contrary, some studies have shown that vegetation restoration can improve fungal diversity by increasing the enzyme activities and soil nutrients [65][66][67]. Our results showed that the AF treatment significantly changed the fungal community structure at the depth of 0-10 cm but did not affect the fungal community's species alpha diversity (Figures 2 and 3).…”
Section: Effects Of Vegetation Restoration On the Soil Fungal Communi...mentioning
confidence: 99%